Study to assess the socio-demographic profile, health status and working conditions of auto-rickshaw drivers in Bhopal - Melwani, Veena; Priya, Angelin; Toppo, Manju; Sethia, Soumitra; Khan, Amreen; Melwani, Satish (International Journal Of Community Medicine And Public Health, 2018)
Background: In India auto-rickshaws are main mode of public transport in urban and areas. Health has always been closely linked with occupation. Auto drivers are exposed to harmful environment like pollutant gases, continuous noise and whole-body vibration as well harmful lifestyle like irregularity of meals, bad posture while driving and stressful occupational conditions due to their working conditions. This study was undertaken to assess the socio-demographic profile, Health status and working conditions of auto-rickshaw drivers. Methods: This cross sectional study was conducted at 15 auto-rickshaw stands of Bhopal city. 20 auto-rickshaw drivers were selected from each stand. A pre designed questionnaire was used to obtain the details of auto-rickshaw drivers. The data was entered in Ms Excel and analysed using Epi info 7. Results: The mean age of study participants was 39.17±10.38 years. 25% of study participants were educated upto 10th std while 22% participants were illiterate. 40.33% of study participants were belonging to lower middle SES. Average no. of customers per day 7, average working hours 12, average income per day on busy day Rs. 420, average income per day on dull day Rs.101. 6.67% of study participants were hypertensive, 3.67% have diabetes while 1% have both HTN and diabetes.12% participants complained of Lacrimation while driving in day. Conclusions: Our study throws some light on working condition and health status of auto-rickshaw drivers. Addiction was common among study participants. There is need for creating awareness regarding health promotion and regular medical check-up.